The Cult of Lares Viales in Asturias - Santos Yanguas, Narciso ('Ilu. Revista de Ciencias de las Religiones, 2012)
Romanization implies, from a religious point of view, a Roman interpretation of indigenous deities by means of a syncretic process. The clearest example is to be found in the indigenous gods of ways, whose existence is known to us through numerous epigraphs and who are assimilated to Roman Lares Viales. Their numbers increase on Asturian soil daily (Tineo, Allande, Lugo de Llanera...) despite the fact that the monuments do not count with «foculi» (holes) for offer deposits.
Keywords: indigenous gods of ways; Lares Viales; syncretic process; Roman interpretation.